The Effect of Eliminating the Affordable Care Act's Tax Credits in Federally Facilitated Marketplaces - Saltzman, Evan (RAND Corporation, 2015)
In this research report, RAND Corporation researchers assess the expected change in enrollment and premiums in the Patient Protection and Affordable Care Act-compliant individual market in federally facilitated marketplace (FFM) states if the U.S. Supreme Court decides to eliminate subsidies in FFM states.